PENENTUAN AWAL BULAN KAMARIAH PERSPEKTIF SYAR'I DAN ILMU PENGETAHUAN - Subaidi Subaidi (LP2M Universitas Ibrahimy, 2015)
The start of the month kamariyah not be done except by rukyatul hilal, either with the naked eye or with the aid of a tool, not the reckoning. Rukyatul is applicable rukyatul global (applies to all Muslims), not the new moon rukyatul applicable locally or regionally on the basis of the concept of mathla'; Is the benchmark rukyatul hilal is rukyatul ruler of Mecca, not absolute rukyatul moon. Unless the ruler of Mecca unsuccessful rukyat moon, then rukyat from another country can be used as a benchmark. Issues related technical rukyatul moon, for example, problem irtifa', should be resolved by consensus of experts to take the most correct opinion (sowab); Do not correct the notion that if rukyat contrary to the reckoning then taken was reckoning. The truth, which is still acceptable rukyat, during testimony meeting the requirements of the testimony. It takes a political institution that can unite the Muslims, it the Khilafah, the caliph's decision will be able to eliminate the difference of opinion, in accordance with the rules of fiqh